Identification des préférences de carrière des étudiants de la Section de la Pédagogie de français - Irfan Nurkhanif, Muhamad; Astuti, Dwi (Universitas Negeri Semarang, 2025)
This research examines the career preferences of seventh-semester students in the French Language Education Undergraduate Program at Universitas Negeri Semarang and the factors influencing them. Using a descriptive quantitative method, a questionnaire was employed to gather data on the students’ career choices. The findings reveal that 39.3% of respondents prefer careers related to French, particularly in tourism, secretarial work, hospitality, and journalism. Approximately 32.8% aspire to become French teachers in formal or non-formal education settings. Additionally, 21.3% consider entrepreneurial activities in language-related fields or ventures combining business and information technology, while 4.9% choose careers in translation and interpretation. Lastly, 1.6% of students pursue other professional paths. Based on Krumboltz’s theory, the primary factors influencing career preferences include specific skills and genetic endowment, environmental conditions, learning experiences, and task accomplishment skills. Thus, it can be concluded that these elements play a significant role in shaping students’ career choices.